Ліквідне забезпечення як запорука якісної кредитної політики комерційного банку: практичний аспект - Добровольська, Олена Володимирівна; Dobrovolska, Olena; Йолтухівський, В. М.; Yoltukhivskiy, V. (Дніпровський державний аграрно-економічний університет, 2021)
У статті розглянуто актуальність питання ліквідного забезпечення, як елемента кредитної політики комерційного банку. Забезпечити ефективність кредитної політики комерційного банку можна, лише за умов підтримання ліквідності забезпечення. Саме тому дослідження і моніторинг ліквідного забезпечення в контексті кредитної політики банку відіграє вагому роль у забезпеченні стабільного функціонування банків та є важливим й актуальним. Підтверджено, що кредитна політика банку передбачає постійне збільшення кредитних ресурсів, підтримання ліквідності кредитного портфеля шляхом покращення якості забезпечення за виданими кредитами по усіх сегментах ринку. Визначено етапи формування та управління портфелем забезпечення АТ «АБ «РАДАБАНК» м. Дніпро. Проаналізовано кредитний портфель та динаміку забезпеченості кредитів АТ «АБ «РАДАБАНК». Запропоновано методи, на яких базується процес управління усіма видами ризику. Надано визначення дефеніції «управління кредитною політикою комерційного банку», як організаційно-економічному процесу функціонування банку задля здійснення кредитування з ціллю досягнення максимальної результативності та мінімізації кредитного ризику. Представлено кредитну політику АТ «АБ «РАДАБАНК» через призму загальних цілей комерційного банку та запропоновано шляхи її здійснення. The article considers the relevance of the issue of liquid collateral as an element of the credit policy of a commercial bank. It is possible to ensure the effectiveness of the credit policy of a commercial bank only if the liquidity of the collateral is maintained. That is why the study and monitoring of liquidity in the context of the bank's credit policy plays an important role in ensuring the stable operation of banks and is important and relevant. It was confirmed that the bank's credit policy provides for a constant increase in credit resources, maintaining the liquidity of the loan portfolio by improving the quality of collateral for loans in all market segments. The stages of formation and management of the portfolio of JSC JSB "RADABANK" Dnipro are determined. The loan portfolio and dynamics of loan collateral of JSC JSB "RADABANK" are analyzed. The loan portfolio of JSC JSB “RADABANK” in 2019 was formed by 38% loans granted for production and construction, 34% - loans for trade, repair of cars, household goods and personal items, 8% each - loans for agriculture , hunting, forestry and loans for real estate transactions, rent, engineering and services, 7% - loans to individuals, 4% - loans for financial services, 1% - loans for other purposes. Considering the types of collateral, legal entities and individuals-entrepreneurs are provided loans, mainly secured by real estate in 2019 increased by +161%, then secured by other assets +286.99%, and lastly, customers provide secured deposit +135.66% in 2019 than in 2015. Methods on which the process of managing all types of risk is based are proposed, namely cyclic and repeated monitoring of mortgaged property, periodic revaluation of mortgaged property, diversification of collateral, experienced legal support, security inspection, such as current debt and re-collateral. compulsory insurance of the subject of the pledge, constant improvement of the qualification of the employees of the mortgage unit. The definition of "credit policy management of a commercial bank" as an organizational and economic process of the bank's operation for lending in order to achieve maximum efficiency and minimize credit risk. It is proved that for a commercial bank the ultimate goals are to make a profit from active operations; ensuring the sustainable operation of the bank and maintaining its reliability. The credit policy of JSC "JSB" RADABANK "through the prism of the general objectives of a commercial bank is presented and the ways of its implementation are suggested.
Liquid provision as a guarantee of quality credit policy of a commercial bank: a practical aspect
Keywords: забезпечення; collateral; ліквідність; liquidity; кредитна політика; credit policy; кредит; credit; кредитний портфель; loan portfolio; кредитний ризик; credit risk; застава; collateral; моніторинг; monitoring